Assessing knowledge, attitude and preventive practices of schistosomiasis among nursing and midwifery students in the Hohoe nursing and midwifery training college, Ghana - Naabil, Divine Tobig; Tsekpo, Desmond; Manyeh, Alfred Kwesi (Frontiers in Tropical Diseases, 2025)
BackgroundSchistosomiasis is a Neglected Tropical Disease of public health importance that is endemic in parts of Africa. With Ghana being part of such areas, it is necessary to assess knowledge, attitude, and preventive methods of schistosomiasis among nursing and midwifery students in the Hohoe Nursing and Midwifery Training College considering the endemicity of the disease in some parts of the region.MethodsA cross-sectional analytical design was used for the investigation knowledge, attitude, and preventive methods of schistosomiasis among nursing and midwifery college students in the Hohoe municipality. STATA 17 was used for analysis and descriptive statistics such as frequencies, proportions, percentages, averages, and standard deviation was utilized to analyze numerical data. Demographic factors associated to respondents’ knowledge, attitudes, and practices were analyzed using logistic regression.ResultsGood knowledge was 84.1% with media being the main source of information on schistosomiasis. There was moderately good attitude of 54.6% towards schistosomiasis. However, Interest in participating in future schistosomiasis prevention and control activities was high (91.7%). Key factors significantly associated with knowledge included Age (AOR = 2.90; 95% CI: 1.60–5.20; p < 0.001), Ethnicity (AOR = 2.00; 95% CI: 1.02–3.80). Preventive practices were strong (90.6%), with Praziquantel recognized as the main treatment.ConclusionWhile students had good knowledge and practices, attitudes were less favorable. Strengthening educational interventions within nursing and midwifery curricula and enhancing student participation in control programs could further improve schistosomiasis prevention.